Improvement and efficiency of business strategy at Kawanseduh coffee by utilizing supply chain management applications - Chrystia Aji Putra; Made Hanindia Prami Swari; Putra Perdana; Wariyanti Nugroho Putri (Jurnal Mantik, 2023)
Kawanseduh Coffee is a growing coffee shop in Surabaya City. Kawanseduh Coffee faces a number of challenges in managing business operations. Some of the main problems are the inability to efficiently record raw materials, manage procurement from suppliers, and make accurate sales predictions. This research discusses Supply Chain Management (SCM) which is built specifically to meet the needs of Kawanseduh Coffee. The implementation of SCM at Kawanseduh Coffee provides good and effective results in improving efficiency in production management, raw material procurement, and inventory management. The features contained in the SCM implementation consist of raw material management, sales features, raw material entry and exit features, and reports consisting of stock reports, receipt reports, and sales reports. The prediction feature in the application has functioned properly and is able to provide an estimate of sales and raw material requirements needed for the following month, based on previously recorded sales data